Development of a real-time PCR method for the specific detection of the novel pear pathogen Erwinia uzenensis - Holeva, Maria C.; Morán, Félix; Scuderi, Giuseppe; Gonzalez, Asier; López, María M.; Llop, Pablo (PLOS, 2019)
Erwinia uzenensis is a plant-pathogenic bacterium, recently described in Japan, which infects pear trees, causing the ‘bacterial black shoot disease of European pear’ (BBSDP). Like other Erwinia pear pathogens, E. uzenensis causes damp, black lesions on young shoots resembling those of E. amylovora, but not blossom blight, fruitlet blight or wilting of the shoot tip. The distribution of E. uzenensis seems restricted to the country where it was reported up to now, but it may spread to other countries and affect new hosts, as is the current situation with E. piriflorinigrans and E. pyrifoliae. Fast and accurate detection systems for this new pathogen are needed to study its biology and to identify it on pear or other hosts. We report here the development of a specific and sensitive detection protocol based on a real-time PCR with a TaqMan probe for E. uzenensis, and its evaluation. In sensitivity assays, the detection threshold of this protocol was 101 cfu ml-1 on pure bacterial cultures and 102–103 cfu ml-1 on spiked plant material. The specificity of the protocol was evaluated against E. uzenensis and 46 strains of pear-associated Erwinia species different to E. uzenensis. No cross-reaction with the non-target bacterial species or the loss of sensitivity were observed. This specific and sensitive diagnostic tool may reveal a wider distribution and host range of E. uzenensis initially considered restricted to a region and will expand our knowledge of the life cycle and environmental preferences of this pathogen.